Cerebral ischemia and asymptomatic coronary artery disease: a prospective study of 83 patients - Di Pasquale, G; Andreoli, A; Pinelli, G; Grazi, P; Manini, G; Tognetti, F; Testa, C (Stroke (1970), 1986)
A prospective cardiologic evaluation was performed in 83 consecutive patients with transient cerebral ischemia or mild stroke and without symptoms or electrocardiographic signs of ischemic heart disease. Patients were studied with an electrocardiographic exercise test; a positive test was followed by exercise Thallium-201 myocardial scintigraphy. Results were compared to those obtained in a group of 83 age and sex-matched healthy subjects submitted to the same study protocol. Asymptomatic coronary artery disease was detected in 28% of cerebrovascular patients with adequate electrocardiographic exercise test. A scintigraphic perfusion defect of variable extension was found in 19 of them. In the control group the electrocardiographic exercise test was positive in only 6% (p less than 0.01). Our results support the concept that: asymptomatic ischemic heart disease is often associated with cerebrovascular disease; therefore cerebral ischemic attacks may be a marker of coronary artery disease, an active investigation of the heart should be considered in cerebrovascular patients in order to plan optimal, comprehensive management.